(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
The purpose of this research is to reveal the nature of the relationship between strategic balancing techniques and their sub-dimensions (strategy, operations, objectives, human resources, and flexibility) and the strategic model for providing security for the Iraqi Ministry of Interior, with its sub-dimensions (the current situation of the Ministry of Interior, the challenges and problems facing the Ministry, security requirements, and the security provision structure. The research adopted a descriptive exploratory approach, presenting the intellectual philosophy of the two variables and then selecting a purposive sample of (289) senior and middle-ranking leaders within the Ministry. These leaders are considered high-ranking, possess strategic vision, and have extensive experience in leadership positions within the Ministry and its formations. The research results are expected to be valuable to the Ministry in guiding it to identify the strengths and weaknesses of its proposed model and its ability to achieve strategic balancing that facilitates the model’s implementation. The statistical software program was used. (SPSS) Through the use of factor analysis to measure the saturation rates of the adopted scale items and to measure the simple and multiple correlation relationship, the research came out with an overall result that there is an inverse correlation relationship between strategic balance techniques and the security provision model of the Ministry of Interior, and that the Ministry’s model failed in the two dimensions (the current situation of the Ministry of Interior, the security provision structure) and its other dimensions succeeded, and the indicators of strategic balance techniques advanced over the indicators of the strategic model for security provision of the Iraqi Ministry of Interior.